2010
DOI: 10.1007/s10334-010-0200-4
|View full text |Cite
|
Sign up to set email alerts
|

MRI-determined carotid artery flow velocities and wall shear stress in a mouse model of vulnerable and stable atherosclerotic plaque

Abstract: Objectives We report here on the pre-clinical MRI characterization of an apoE−/− mouse model of stable and vulnerable carotid artery atherosclerotic plaques, which were induced by a tapered restriction (cast) around the artery. Specific focus was on the quantification of the wall shear stress, which is considered a key player in the development of the plaque phenotype. Materials and methods In vivo MRI was performed at 9.4 T. The protocol consisted of time-of-flight angiography, highresolution T1-and T2-weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…11 Although it is generally assumed that the average ESS over the cardiac cycle in large straight arteries experiencing laminar flow remains at a physiological level of ≈15 to 20 dynes/cm 2 , the value of ESS varies within the arterial tree and is inversely related to vessel diameter and species size. 45 Similar to our data and despite the interspecies differences in the absolute ESS values, low in vivo ESS has been found in (1) mice upstream of a cast, placed to cause vessel obstruction, at the position where plaques with vulnerable histological features develop (112±52 dynes/cm 2 ), 22 as measured by MRI; (2) high-risk swine coronary arteries (<10 dynes/cm 2 ), as measured by IVUS 10,23 ; and (3) human coronary arteries exhibiting progression and in-stent restenosis (<9.1 dynes/ cm 2 ), as measured by IVUS. 14 Because plaque disruption is a complex process, comprehensive plaque vulnerability assessment should involve a combination of systemic markers, plaque morphological features, hemodynamic conditions, and biomechanical factors.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…11 Although it is generally assumed that the average ESS over the cardiac cycle in large straight arteries experiencing laminar flow remains at a physiological level of ≈15 to 20 dynes/cm 2 , the value of ESS varies within the arterial tree and is inversely related to vessel diameter and species size. 45 Similar to our data and despite the interspecies differences in the absolute ESS values, low in vivo ESS has been found in (1) mice upstream of a cast, placed to cause vessel obstruction, at the position where plaques with vulnerable histological features develop (112±52 dynes/cm 2 ), 22 as measured by MRI; (2) high-risk swine coronary arteries (<10 dynes/cm 2 ), as measured by IVUS 10,23 ; and (3) human coronary arteries exhibiting progression and in-stent restenosis (<9.1 dynes/ cm 2 ), as measured by IVUS. 14 Because plaque disruption is a complex process, comprehensive plaque vulnerability assessment should involve a combination of systemic markers, plaque morphological features, hemodynamic conditions, and biomechanical factors.…”
Section: Discussionsupporting
confidence: 87%
“…Of the 134 vascular segments studied, 28 contained thrombus (disrupted) and 106 did not (nondisrupted [14][15][16] or low ESS and histological evidence of plaque instability. 10,12,13,17,18,22 However, only limited studies using invasive IVUS have investigated the association among low ESS, plaque progression, vascular remodeling, and plaque vulnerability, and have tested the feasibility of these measurements to predict plaque growth and instability. 14,23 MRI has evolved as a noninvasive imaging modality to visualize the vessel wall with high spatial resolution in humans [24][25][26] and animal models.…”
Section: Clinical Perspective On P 310mentioning
confidence: 99%
“…If in preclinical studies TOF-MRA is widely used for the characterization of cerebral vasculature, it has also been applied with success to various murine models of cardiovascular disease, including mice with carotid artery ligation [71,145,149], hindlimb ischemia [71], aortic aneurysms [82,83] and/or mice with a hyperlipidemic pattern [149]. A TOF 3D angiogram of the aortic root obtained in a mouse model of aortic banding on an 11.7 T MRI machine is shown in Fig.…”
Section: Time Of Flight Angiographymentioning
confidence: 99%
“…The association between low WSS and atherosclerosis is now widely accepted, and efforts are being made to provide imaging techniques that enable it to be measured in vivo. 122 Low WSS has been shown to upregulate both adhesion molecules that attract leukocytes and growth factors that promote smooth-muscle cells to proliferate and migrate. 2 Using porcine culture endothelial cells, Warboys et al 123 showed that acute application (1 hour) of shear stress increases the permeability of the endothelial monolayer, whereas chronic application (1 week) induces the opposite phenomenon, reducing the permeability and therefore the infiltration of macromolecules responsible for plaque formation.…”
Section: Plaque Formationmentioning
confidence: 99%